2020
DOI: 10.1161/jaha.119.014717
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning–Based Algorithm for Detecting Aortic Stenosis Using Electrocardiography

Abstract: Background Severe, symptomatic aortic stenosis ( AS ) is associated with poor prognoses. However, early detection of AS is difficult because of the long asymptomatic period experienced by many patients, during which screening tools are ineffective. The aim of this study was to develop and validate a deep learning–based algorithm, combining a multilayer perceptron and convolutional neural network, for detecting significant AS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
88
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 35 publications
0
88
0
2
Order By: Relevance
“…Attia et al developed deep-learning algorithms for screening cardiac contractile dysfunction, predicting the occurrence of atrial fibrillation during sinus rhythm, approximating age and sex, and detecting hyperkalemia using raw ECG data and demonstrated its feasibility 11,12,24,25 . Our study showed that a deep-learning-based algorithm using ECG could outperform cardiologists in diagnosing left ventricular hypertrophy and valvular heart disease 14,15,26,27 . We used a sensitivity map to visualize the regions of the ECGs that were used for decision-making by the DLA.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Attia et al developed deep-learning algorithms for screening cardiac contractile dysfunction, predicting the occurrence of atrial fibrillation during sinus rhythm, approximating age and sex, and detecting hyperkalemia using raw ECG data and demonstrated its feasibility 11,12,24,25 . Our study showed that a deep-learning-based algorithm using ECG could outperform cardiologists in diagnosing left ventricular hypertrophy and valvular heart disease 14,15,26,27 . We used a sensitivity map to visualize the regions of the ECGs that were used for decision-making by the DLA.…”
Section: Discussionmentioning
confidence: 81%
“…Deep learning is a type of artificial intelligence approach that extracts and uses meaningful patterns from complex digital data and has recently been used to analyze ECGs for diagnosing an arrhythmia, heart failure, left ventricular hypertrophy, valvular heart disease, age, and sex [11][12][13][14][15][16] . To develop a reliable MI detecting method based on ECG, we used deep learning.…”
mentioning
confidence: 99%
“…Furthermore, these previous studies all focus on prediction, but specific ECG patterns used by DNNs are rarely visualized. 3 , 5 8 Visualization of such features takes advantage of the feature discovery embedded in DNNs and will help clinicians to interpret ECGs more accurately and possibly facilitate discovery of novel features.…”
mentioning
confidence: 99%
“…The application of deep learning technology in the cardiovascular eld for arrhythmias, dyskalemia, and valvular heart disease had become popularized recently. [19][20][21][27][28][29] However, no large scale study has been designed to apply deep learning technology for MI detection. Previous DLMs for MI detection by ECG were analyzed mainly from the Physikalisch-Technische Bundesanstalt (PTB) diagnostic ECG Database.…”
Section: Discussionmentioning
confidence: 99%